2003
DOI: 10.1253/circj.67.515
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Evoked QT Intervals According to Variations in Atrioventricular Delay and Cardiac Function in Patients With Implanted QT-Driven DDDR Pacemakers

Abstract: In patients with implanted DDD pacemaker, cardiac output is maximal when atrioventricular (AV) delay is set to give the maximum QT interval (QTI). QTI is used as a sensor of a rate-responsive pacemaker and the evoked QTI (eQTI) is measured as the time duration from the ventricular pace-pulse and the T sense point, which is the steepest point of the intracardiac T wave. The relationship between the changes in eQTI according to AV delay variations and cardiac function was studied in 13 patients (74.2+/-9.3 [SD] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…[14][15][16][17] In the present study, we observed that the correlation between the amplitude of S1 and the length of the AV delay was represented as a cubic curve. Furthermore, the AV delay at the inflection point of this cubic curve showed a significant positive correlation with the optimal AV delay determined by echocardiography (R=0.925, P<0.005).…”
Section: Discussionsupporting
confidence: 61%
“…[14][15][16][17] In the present study, we observed that the correlation between the amplitude of S1 and the length of the AV delay was represented as a cubic curve. Furthermore, the AV delay at the inflection point of this cubic curve showed a significant positive correlation with the optimal AV delay determined by echocardiography (R=0.925, P<0.005).…”
Section: Discussionsupporting
confidence: 61%
“…Under exercise or stress conditions, myocardial contractility increases in response to autonomic nervous system regulation, resulting in a change in the duration of the QT interval corresponding to the period of ventricular repolarization [ 70 , 71 , 72 ]. The atrioventricular interval, depending on the native atrioventricular conduction time or the programmed A-V interval settings on the pacemaker, is also closely related to the QT interval [ 73 , 74 , 75 , 76 ]. Recent studies describe the phenomenon of QT adaptation as an abrupt change in the rate or interruption of atrial and ventricular pacing; this is indicative of the complexity of the phenomenon and the existence of many potential factors (extrinsic, such as pacing, and intrinsic, such as pharmacotherapy of conduction dysfunctions, electrolyte disturbances, or short- or long-QT syndromes) that can affect this parameter [ 77 , 78 , 79 , 80 , 81 ].…”
Section: Rate Response In Implantable Cardiac Pacemakersmentioning
confidence: 99%